2020
DOI: 10.1186/s12885-020-07410-2
|View full text |Cite
|
Sign up to set email alerts
|

A high neutrophil-to-lymphocyte ratio is a poor prognostic factor for castration-resistant prostate cancer patients who undergo abiraterone acetate or enzalutamide treatment

Abstract: Background Inflammatory cytokine markers, including the neutrophil-to-lymphocyte ratio (NLR), monocyte-lymphocyte ratio, and platelet-to-lymphocyte ratio, play important roles as prognostic markers in several solid malignancies, including prostate cancer. We previously reported the NLR as a poor prognostic marker in bladder cancer, upper-urothelial carcinoma, adrenocortical carcinoma, penile cancer, and prostate cancer. This study examined the importance of the NLR as a prognostic marker for castration-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Systemic immunity and cancer‐related inflammation are effective on prognosis in patients with cancer 13 . The effects of inflammatory markers neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) on prognosis in patients mCRPC treated with abiraterone or enzalutamide were evaluated 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic immunity and cancer‐related inflammation are effective on prognosis in patients with cancer 13 . The effects of inflammatory markers neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) on prognosis in patients mCRPC treated with abiraterone or enzalutamide were evaluated 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings regarding the role of systemic immunity in patients with mCRPC, Fan et al 18 concluded that the systemic‐immune‐inflammation index, calculated by using lymphocyte, neutrophil, and platelet, had a prognostic role in those patients treated with AA and docetaxel. Furthermore, Kawahara et al 13 showed that NLR was prognostic in patients with mCRPC treated with AA or enzalutamide. It should be noticed that PIV includes four systemic inflammation indicators and may better represent the systemic inflammation in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, focal tumor immune responses show possible association with the systemic immune responses in cancer patients (25,27). Studies show that changes in systemic inflammation environment, such as NLR, can be a useful biomarker for predicting the survival of cancer patients (25,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In the era of numerous genetic prognostic factors in bladder cancer [25][26][27][28], there is an urgent need for easily accessible, affordable, and widely interpretable biomarkers for current practice. The Neutrophil-to-lymphocyte Ratio proves to have all these benefits [29][30][31].…”
Section: Discussionmentioning
confidence: 99%